2016
DOI: 10.1136/oemed-2016-103769
|View full text |Cite
|
Sign up to set email alerts
|

Risk of renal cell carcinoma following exposure to metalworking fluids among autoworkers

Abstract: Objectives Metalworking fluids (MWF), used to cool and lubricate metal in occupational settings, are linked to several cancers but data on kidney cancer are limited. We examine how MWF influence the rate of renal cell carcinoma (RCC) in a large prospective study. Methods A cohort of Michigan autoworkers consisting of 33,421 individuals was followed 1985 through 2009. The cohort was linked to the Michigan Cancer Registry to identify new cases of RCC. We analyzed RCC in relation to cumulative exposure to each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Another cohort study on the effect of metalworking fluids as RCC risk factor which recruited 33,421 workers also found that there were only 13.5% of female workers. Both 2,4,5-T herbicide and metalworking fluids exposures were shown to be associated with increased risk for RCC (Andreotti et al, 2020;Shrestha et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Another cohort study on the effect of metalworking fluids as RCC risk factor which recruited 33,421 workers also found that there were only 13.5% of female workers. Both 2,4,5-T herbicide and metalworking fluids exposures were shown to be associated with increased risk for RCC (Andreotti et al, 2020;Shrestha et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The authors enrolled 57,310 individuals seeking licenses to apply for restricted-use pesticides in Iowa and North Carolina between 1993 and 1997, of whom only about 2.7% were female [29]. Similarly, in a study presenting a dose-dependent association between RCC and exposure to metalworking fluids among autoworkers, the cohort consisted of 33,421 individuals, of whom 86.5% were males [30].…”
Section: Smoking and Occupational Hazardmentioning
confidence: 99%
“…Although studies on occupational exposure limits for MWF have been published [ 8 , 9 ], there are no set thresholds for cumulative exposure. Shrestha et al have supposed that long-term exposure to MWF aerosols correlates with kidney cancer and glomerulonephritis [ 10 , 11 ]. According to previous research, MWF aerosols contain sulfonates, nonionic surfactants, ethanolamine, medium-chained chlorinated paraffins (MCCPs), and polycyclic aromatic hydrocarbons (PAHs) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%